An Improved Synthesis of Water-Soluble Dual Fluorescence Emission Carbon Dots from Holly Leaves for Accurate Detection of Mercury Ions in Living Cells - Wang P (Dove Medical Press, 2021)
Pengchong Wang,1,2 Yan Yan,1,2 Ying Zhang,2 Tingting Gao,2 Hongrui Ji,2 Shiyan Guo,2 Ke Wang,2 Jianfeng Xing,2 Yalin Dong1 1Department of Pharmacy, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, 710061, People’s Republic of China; 2School of Pharmacy, Xi’an Jiaotong University, Xi’an, 710061, People’s Republic of ChinaCorrespondence: Yalin Dong; Jianfeng Xing Email dongyalin@mail.xjtu.edu.cn; xajdxjf@mail.xjtu.edu.cnBackground: Carbon dots (CDs) emitting near-infrared fluorescence were recently synthesized from green leaves. However, the Hg2+ detection of CDs was limited because of the insufficient water solubility, low fluorescence and poor stability.Methods: Dual fluorescence emission water-soluble CD (Dual-CD) was prepared through a solvothermal method from holly leaves and low toxic PEI1.8k. PEG was further grafted onto the surface to improve the water solubility and stability.Results: The Dual-CD solution can emit 487 nm and 676 nm fluorescence under single excitation and exhibit high quantum yield of 16.8%. The fluorescence at 678 nm decreased remarkably while the emission at 470 nm was slightly affected by the addition of Hg2+. The ratiometric Hg2+ detection had a wide linear range of 0– 100 μM and low detection limit of 14.0 nM. In A549 cells, there was a good linear relation between F487/F676 and the concentration of Hg2+ in the range of 0– 60 μM; the detection limit was 477 nM. Furthermore, Dual-CD showed visual fluorescence change under Hg2+.Conclusion: Dual-CD has ratiometric responsiveness to Hg2+ and can be applied for quantitative Hg2+ detection in living cells.Keywords: chlorophyll, polyethyleneimine, polyethylene glycol, ratiometric Hg2+ detection, A549 cells